Testing: Methodology and Quality Indicators - Zubanova, Svetlana (2020)
Testing is a modern high-quality method of knowledge check. Informatization which began in the late XX – early XXI century contributed to the growth of various tests. However, the inclusion of tests in the educational process is at a slower pace. This is largely due to the lack of a methodological basis for test development. It is proved that the test control methodology is an interdisciplinary theory that combines the achievements of pedagogy, psychology, measurement theory, quality theory, statistics, mathematics, organization and management theory. The article describes the principle of the testing methodology; the type and kinds of tests are determined, as well as the methodological principles for high-quality text creation. The criteria are described that must be met by tests: relations with education and training, objectivity, systematicity and comprehensive nature, relevance, the relationship of increasing difficulty content and form, and test optimality.